Modelagem matemática e simulação dinâmica de um forno de cal com alimentação de lama seca - Barbara Bulgarelli Alves de Aguiar (2016)
The rotary kiln has been used extensively in various industrial processes and inside several transformations may occur, for example, heating, drying, reduction reactions, such as calcination and cooling. For a good kiln operation a good understanding of the process is necessary, and the lime kiln in the pulp mill, has proven to be challenging to present several problems that are linked to the operation mode, the inefficiency of previous processes, the presence of elements that have no active participation in the process (Mg, Mn, Fe, K, S, P, among others) and attempts to replace the use of fossil fuels by alternative fuels without proper study. The mathematical modeling and simulation have been helping in the process understanding, design improving and operation of the kiln, making them more efficient. This study aims to present the development of the modeling and dynamic simulation of a lime kiln for the pulp mill. The model is represented by a system of partial differential equations, considering the mass and energy balances of the process, as well as additional equations. This system of equations is solved by the Method of Lines (MOL) with discretization by finite differences of the spatial direction and integration of ordinary differential equations (ODE) resulting in Matlab software. The model predicts the dynamic temperature profile of the gas phase and the solid bed, as well as the behavior of the calcination reaction. The data were compared with the literature, and model could satisfactorily describe the lime kiln.